Mudanças na estrutura do comércio exterior brasileiro: uma análise sob a ótica da teoria de Heckscher-Ohlin - Feistel, Paulo Ricardo; Hidalgo, Álvaro Barrantes (Estudos Econômicos (São Paulo), 2013)
The objective of this study is to analyze the changes in the Brazilian foreign trade structureafter the liberalization trade in terms of use of the available productive resources.The analysis is performed based on the factors proportions theory, in model of three factors: labor, natural resources and capital. Using the technique of input-output ismeasured the content of the trade productive factors while it is analyzed the long-termtrend tendencies of Brazilian economic specialization in comparatives advantages termsaccording to Heckscher-Ohlin theory. The results show a long-term trend of increasedparticipation of resource-intensive products beyond a decrease in the participation ofthe intensive products in capital and labor in Brazilian exports. On the other hand asthey relate to imports, these show a clear trend in the increasing of intensive productsin capital and a decrease in the participation of intensive products in natural resources,therefore consistent with the principles of comparative advantages of Heckscher-Ohlin.